2010-2014 Seismic activity images the activated fault system in the Pollino area, at the Appennines-Calabrian arc boundary region - Pasquale De Gori; Lucia Margheriti; Francesco Pio Lucente; Aladino Govoni; Milena Moretti; Marina Pastori; Alessandro Marchetti; Rita Di Giovanbattista; Mario Anselmi; Paolo De Luca; Anna Nardi; Nicola Piana Agostinetti; et al. (2014)
2010-2014 Seismic activity images the activated fault system in the Pollino area, at the Appennines-Calabrian arc boundary region